Effectiveness of endorsement in context of self congruency. - Yew, Leiching. (2010)
Celebrity endorsements have been traditionally hailed to be more effective than other types of endorsers. However, there are increasing examples of successful advertisement campaigns that did not employ Celebrities, which leads us to rethink if this theory still holds true in the evolving business world. On the other hand, effects of self-congruency in consumer behavior have been increasingly explored. This leads us to take another look at the topic, in the context of the consumers’ self concepts. The objective of this project is to investigate if Celebrity endorsers could generate a higher Brand Interest, Purchase Intention, better Attitude toward the Advertisement and better Attitude toward the Brand when the viewers’ Ideal Self is salient, and vice versa for Typical Consumer Endorsers when the viewers’ Actual Self is salient. 100 respondents were selected to participate in a 2 by 2 experiment where the respondents’ were primed to activate their Actual or Ideal Selves, and subsequently shown a hypothetical advertisement featuring either a Celebrity or Typical Consumer endorser.